2016
DOI: 10.3171/2015.12.spine151085
|View full text |Cite
|
Sign up to set email alerts
|

Uremic tumoral calcinosis in the cervical spine: case report

Abstract: Tumoral calcinosis is an uncommon condition characterized by the calcification of periarticular soft tissue. In uremic patients the disease is secondary to metabolic disturbances in predisposed patients. The authors report the case of a 73-year-old woman who presented with a new painful cervical mass while undergoing continuous ambulatory peritoneal dialysis for long-standing end-stage renal disease (ESRD). A CT scan of the neck showed a lobulated, calcified mass in the left paraspinal soft tissue at C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The exact mechanism of UTC is still unknown,so no approved effective therapy currently exists.Surgery may not be the rst option due to the presence of multiple co-morbidities and higher risk of recurrence,the underlying disorder is primarily treated [30][31] .A low-phosphate diet is an essential rst step,primary treatment modalities consists of phosphate binders [32][33] and antacids, if this is ineffective,increasing urinary phosphate excretion by the administration of acetazolamide might be bene cial [34] ,this has been shown to reduce size of TC lesions to various degrees. Sevelamer may result in a decrease in serum phosphate level,but the response in the described cases in the literature was inconsistent,the bene ts are limited and it could not prevent the progression of the lesion [35] .Medical therapy is also used for TC patients,using low-calcium dialysate solutions, high-ux hemodialysis and increased length and frequency of hemodialysis treatments [36] .Fatehi et al [37] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.Surgical resection should be considered when calcinosis causes severe pain, neurologic dysfunction or joint function limitations [38] .In addition,parathyroidectomy and renal transplantation have been performed,the role of parathyroidectomy is still controversial [39] ,it usually achieves remarkable resolution in dialysis patients with severe hyperparathyroidism and elevated serum alkaline phosphatase(ALP) [40] ,but in the absence of secondary hyperparathyroidism with a markedly elevated PTH, parathyroidectomy should be avoided as it may not improve calcium and phosphorus control or favorably affect the underlying process [41] .Successful renal transplantation can provides complete resolution of UTC by inducing a negative calcium balance [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of UTC is still unknown,so no approved effective therapy currently exists.Surgery may not be the rst option due to the presence of multiple co-morbidities and higher risk of recurrence,the underlying disorder is primarily treated [30][31] .A low-phosphate diet is an essential rst step,primary treatment modalities consists of phosphate binders [32][33] and antacids, if this is ineffective,increasing urinary phosphate excretion by the administration of acetazolamide might be bene cial [34] ,this has been shown to reduce size of TC lesions to various degrees. Sevelamer may result in a decrease in serum phosphate level,but the response in the described cases in the literature was inconsistent,the bene ts are limited and it could not prevent the progression of the lesion [35] .Medical therapy is also used for TC patients,using low-calcium dialysate solutions, high-ux hemodialysis and increased length and frequency of hemodialysis treatments [36] .Fatehi et al [37] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.Surgical resection should be considered when calcinosis causes severe pain, neurologic dysfunction or joint function limitations [38] .In addition,parathyroidectomy and renal transplantation have been performed,the role of parathyroidectomy is still controversial [39] ,it usually achieves remarkable resolution in dialysis patients with severe hyperparathyroidism and elevated serum alkaline phosphatase(ALP) [40] ,but in the absence of secondary hyperparathyroidism with a markedly elevated PTH, parathyroidectomy should be avoided as it may not improve calcium and phosphorus control or favorably affect the underlying process [41] .Successful renal transplantation can provides complete resolution of UTC by inducing a negative calcium balance [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy is also used for TC patients, especially for UTC patients using aggressive phosphate binders, calcimimetics, using low-calcium dialysate solutions, and increased length and frequency of hemodialysis treatments [ 28 ]. Fatehi et al [ 8 ] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…12 In contrast to the commonly painless and asymptomatic presentation of its extraspinal counterparts, spinal tumoral calcinosis often presents with pain or neurological deficits. [3][4][5] Tumoral calcinosis can arise in patients with underlying genetic or metabolic disorders that result in hyperphosphatemia, 19 uremia, 3,4,20 scleroderma, 5,13,18,21 rheumatoid arthritis, 22 and seronegative spondyloarthropathy. 12 Idiopathic cases have been reported [9][10][11]16,23,24 as well as those arising secondary to surgery or trauma at the site of involvement.…”
Section: Observationsmentioning
confidence: 99%